2021
DOI: 10.1200/po.20.00428
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Free DNA Detection of Tumor Mutations in Heterogeneous, Localized Prostate Cancer Via Targeted, Multiregion Sequencing

Abstract: PURPOSE Cell-free DNA (cfDNA) may allow for minimally invasive identification of biologically relevant genomic alterations and genetically distinct tumor subclones. Although existing biomarkers may detect localized prostate cancer, additional strategies interrogating genomic heterogeneity are necessary for identifying and monitoring aggressive disease. In this study, we aimed to evaluate whether circulating tumor DNA can detect genomic alterations present in multiple regions of localized prostate tumor tissue.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
2
4
0
Order By: Relevance
“…Although the target gene sequencing via liquid biopsy for nmPCa is hampered by the low overall abundance of ctDNA [22], we found that ctDNA was detectable 65.5% of the studied patients, which is consistent with a previous study that has reported the variant detection rate of 57% [23]. Additionally, the clinicopathological features including PSA, Gleason score and clinical stage were not strongly associated with the ctDNA status in the present study, but the patients with aggressive disease subtypes tended to have detectable ctDNA.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although the target gene sequencing via liquid biopsy for nmPCa is hampered by the low overall abundance of ctDNA [22], we found that ctDNA was detectable 65.5% of the studied patients, which is consistent with a previous study that has reported the variant detection rate of 57% [23]. Additionally, the clinicopathological features including PSA, Gleason score and clinical stage were not strongly associated with the ctDNA status in the present study, but the patients with aggressive disease subtypes tended to have detectable ctDNA.…”
Section: Discussionsupporting
confidence: 92%
“…Specially, we observed that ctDNA samples shared no concurrent alteration with tumor samples. As ctDNA proves to have the potential ability to capture both likely clonal and subclonal alterations from multiple tumor cell populations [23], our results substantially support that ctDNA reflecting the comprehensive mutational status could be used in the evaluation of heterogeneous nmPCa.…”
Section: Discussionsupporting
confidence: 70%
“…Our study also chiefly used Mutect2 as the main variant caller due to its sensitivity in detecting low VAF (<1%) somatic mutations. 63 , 64 , 65 While low VAF mutations are more challenging to experimentally validate, our data suggests that a substantial number of these mutations are of functional significance, through integration of existing databases ( STAR methods ), exhibition of mutational signatures similar to higher VAF mutations ( Figures S1 E and S1F), and being rarely identified in control blood samples subjected to the same sequencing and analysis pipeline ( STAR methods ). A third limitation was that while we were able to validate the presence of several IM driver genes in an independent cohort, the current lack of other large-scale IM genomic datasets with mature follow-up information prevented us from independently validating the genome-clinical predictive models.…”
Section: Discussionmentioning
confidence: 84%
“…In its turn, ctDNA may be an object for identifying clinically relevant genomic alterations and tumor subclones. Thus, in the study by Chen et al [ 45 ], somatic tissue alterations were identified in ctDNA derived from the blood plasma of PCa patients with localized prostate cancer, in 57% of cases, including such alterations as nonsynonymous variants in FOXA1, PTEN, MED12, and ATM.…”
Section: Cell-free Dna (Cfdna)mentioning
confidence: 99%